2022
DOI: 10.3390/ijerph20010373
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Spatial Coupling Coordination Development: Identifying Land System States from the Adaptation–Conflict Perspective

Abstract: With the advancement of global urbanization, ecosystem conservation and sustainable land development have become major issues. In this context, the uncoordinated and imbalanced development of the land-centered human–environment system requires urgent attention, especially in rust belt cities that pose critical challenges to regional land system sustainability. Therefore, taking Changchun City from 1990 to 2020 as an example, we identified and evaluated the ecosystem service (ES) balance and land use conflict f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The so-called three-area space (hereinafter referred to as "three-area space") refers to the urban space, agricultural space, and ecological space that directly to the geographical function division and development strategy requirements of urban development, food security, and ecological environmental protection in the provincial main function zones (Wang et al, 2023;, they serve as important technology approach for undertaking macro-scale (main function zones) and micro-scale (land use). Moreover, it aligns with the 11th goal of United Nations' Sustainable Development Goals (SDGs) "Build inclusive, safe, risk-resistant and sustainable cities and human settlements" released in 2015 (Allen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The so-called three-area space (hereinafter referred to as "three-area space") refers to the urban space, agricultural space, and ecological space that directly to the geographical function division and development strategy requirements of urban development, food security, and ecological environmental protection in the provincial main function zones (Wang et al, 2023;, they serve as important technology approach for undertaking macro-scale (main function zones) and micro-scale (land use). Moreover, it aligns with the 11th goal of United Nations' Sustainable Development Goals (SDGs) "Build inclusive, safe, risk-resistant and sustainable cities and human settlements" released in 2015 (Allen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that ecosystems with simple food chain structures and low biodiversity indices are relatively vulnerable (Peng et al, 2020). From the perspective of landscape ecology and concerning existing results (Zhou et al, 2015a), the landscape vulnerability of the "three-zone spaces" is ranked from strong to weak as urban space, agricultural space, and ecological space (Wang et al, 2023); (Table 3). 3) Spatial stability index (SI): In general, the higher the degree of fragmentation of the spatial pattern of the landscape, the less stable and the stronger the spatial conflict (Jiang S et al, 2021), while the fragmentation of land use type patches is reflected in the clustering and increasing density of point-like space or the diffusion of linear space and the fragmentation of face-like patch space (Wang et al, 2023).…”
Section: ) Spatial Complexity Index (Ci)mentioning
confidence: 98%
“…From the perspective of landscape ecology and concerning existing results (Zhou et al, 2015a), the landscape vulnerability of the "three-zone spaces" is ranked from strong to weak as urban space, agricultural space, and ecological space (Wang et al, 2023); (Table 3). 3) Spatial stability index (SI): In general, the higher the degree of fragmentation of the spatial pattern of the landscape, the less stable and the stronger the spatial conflict (Jiang S et al, 2021), while the fragmentation of land use type patches is reflected in the clustering and increasing density of point-like space or the diffusion of linear space and the fragmentation of face-like patch space (Wang et al, 2023). Therefore, patch density (PD) is usually chosen to measure the land use stability index, with higher patch density leading to higher spatial fragmentation and therefore lower spatial stability (Table 3).…”
Section: ) Spatial Complexity Index (Ci)mentioning
confidence: 99%
See 2 more Smart Citations